2014
DOI: 10.1007/s12013-014-9936-1
|View full text |Cite
|
Sign up to set email alerts
|

Late Remote Ischemic Preconditioning Provides Benefit to Patients Undergoing Elective Percutaneous Coronary Intervention

Abstract: To assess whether late remote ischemic preconditioning (L-RIPC) is effective in myocardial protection in patients with ischemic heart disease undergoing elective percutaneous coronary intervention (PCI). L-RIPC is exerted by newly synthesized cardioprotective proteins. The cardioprotective effects of L-RIPC are more durable. 200 consecutive patients undergoing elective PCI were randomized to receive L-RIPC (induced by three 5-minute inflations of a blood pressure cuff to 200 mmHg around the upper arm, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
2
18
0
1
Order By: Relevance
“…The continuous presence of a circulating factor that provides cardioprotection in the bioassay mouse heart in the present study is again consistent with prior experimental and clinical studies, which revealed evidence of long-lasting protection 24, 26, 27, 39 for up to 1 week after the RIPC stimulus (28). In contrast to our present study, however, these studies could not distinguish between a long-lasting presence of a circulating factor or a long-lasting protective effect in the target organ.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The continuous presence of a circulating factor that provides cardioprotection in the bioassay mouse heart in the present study is again consistent with prior experimental and clinical studies, which revealed evidence of long-lasting protection 24, 26, 27, 39 for up to 1 week after the RIPC stimulus (28). In contrast to our present study, however, these studies could not distinguish between a long-lasting presence of a circulating factor or a long-lasting protective effect in the target organ.…”
Section: Discussionsupporting
confidence: 91%
“…Prior studies have reported a time delay between the RIPC stimulus and the injurious event from 5 to 10 min 22, 23 to more than 24 h 24, 25, 26, 27, suggesting that RIPC is a fast acting as well as a long-lasting phenomenon. Supporting the notion of a long-lasting effect, flow-mediated forearm vasodilation in patients with reperfused acute myocardial infarction was improved by RIPC for 1 week (28).…”
mentioning
confidence: 97%
“…A retrospective analysis of the CONDI trial (Effect of Remote Ischemic Conditioning on Clinical Outcome in (Table 3). A similar pattern with infarct size reduction in the majority but not all studies (with 2 small extreme outlier studies reporting even increased infarct size by remote ischemic preconditioning 114,115 ) emerged for elective PCI when either remote ischemic pre- [116][117][118][119][120][121][122][123] or postconditioning 124,125 was used for cardioprotection. In some of these studies, clinical outcome was reported as a secondary outcome, and it was either not different 106,119,124 or improved.…”
Section: Remote Ischemic Conditioningmentioning
confidence: 66%
“…Prasad et al [28] used a different protocol and delivered 3 cycles of 3-minute ischemia/reperfusion immediately before PCI, but they were not able to show cardioprotection. Unlike the studies of classical preconditioning, Liu et al demonstrated that late RIPC also had beneficial effects on patients undergoing elective PCI [29]. Although there is heterogeneity in RIPC protocols, meta-analyses of the major RIPC studies in elective PCI indicated that ischemic preconditioning had beneficial effects on post-PCI myocardial injury [3133].…”
Section: Discussionmentioning
confidence: 99%